Relationship between fragmented QRS complexes and ejection fraction recovery in anterior ST-segment elevation myocardial infarction patients undergoing thrombolytic treatment. Issue 5 (August 2020) - Eren, Hayati; Kaya, Ülker; Öcal, Lütfi; Gürbüz, Ahmet Seyfeddin; Kalçik, Macit; Abaci, Adnan
Abstract : Background: Acute anterior ST-segment elevation myocardial infarction (STEMI) is a life-threatening disease. Adverse cardiac events of acute anterior STEMI include cardiovascular death or worsening congestive heart failure. This study investigated the role of fragmented QRS complex (fQRS) in predicting insufficient ejection fraction (EF) recovery in acute anterior STEMI. Methods: Patients with acute anterior STEMI who received thrombolytic therapy were prospectively enrolled in this study. Twelve-lead electrocardiography (ECG) was obtained from all patients during admission and 24 and 48 h after admission. We divided the patients into two groups according to the presence of fQRS appearance within 48 h: absence of fQRS in any lead (fQRS−), and its presence in two or more contiguous leads (fQRS+). All patients were evaluated with transthoracic echocardiography at admission, and at follow-up 6 and 12 months later. Results: A total of 138 consecutive patients were included in the study. Seventy-three patients (52.9%) had fQRS in the ECG. EF recovery in the fQRS(+) group was significantly lower than that of the fQRS(−) group (39% vs. 43.9%, P < 0.001). Multiple logistic regression analysis showed that the fQRS (odds ratio: 4.147, 95% confidence interval: 1.607–10.697, P = 0.003) were an independent predictor of poor EF recovery. Conclusion: The presence of fQRS is an independent predictor for inadequate EF recovery in acute anterior STEMI patients undergoing thrombolytic treatment. Assessment of fQRS on surface ECG may be used in determining high-risk patients for poor EF recovery after acute anterior STEMI.